2015
DOI: 10.1007/s00436-015-4366-6
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptosporidium and Giardia in recycled waters used for irrigation and first description of Cryptosporidium parvum and C. muris in Greece

Abstract: Here, we present the first time findings regarding the occurrence of Cryptosporidium and Giardia in sewage waters and the first molecular characterization of Cryptosporidium species in Greece. Biological treatment plants from three regions in Greece have been investigated. The detection of Cryptosporidium oocysts was by modified Ziehl-Neelsen acid fast (MZN-AF) and by immunofluorescence microscopy (IFT) for Cryptosporidium and Giardia (oo)cysts, whereas nested PCR based on the SSU rDNA assay was used for molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Carducci and Verani showed the presence of adenovirus DNA in 100 % of collected samples, while an average reduction of 2 log was recorded (Carducci and Verani 2013). Similarly, AdVs were detected in 100 % of wastewater and sewer overflows (CSOs) For Cryptosporidium and Giardia spp., please refer to Spanakos et al (2015); units: E. coli, log 10 MPN/L; TC, log 10 MPN/L; bacteriophages, log 10 plaque forming units (PFU)/L; hAdVs, log 10 GC/L discharge samples in the study of Fong et al (2010). Average adenovirus DNA concentrations in sewage and CSOs were 1.15×10(6) viruses/liter and 5.35×10(5) viruses/liter, respectively, while the adenovirus removal was calculated at <2 log(10) (99 %) for this WWTP (Fong et al 2010).…”
Section: Microbiological Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Carducci and Verani showed the presence of adenovirus DNA in 100 % of collected samples, while an average reduction of 2 log was recorded (Carducci and Verani 2013). Similarly, AdVs were detected in 100 % of wastewater and sewer overflows (CSOs) For Cryptosporidium and Giardia spp., please refer to Spanakos et al (2015); units: E. coli, log 10 MPN/L; TC, log 10 MPN/L; bacteriophages, log 10 plaque forming units (PFU)/L; hAdVs, log 10 GC/L discharge samples in the study of Fong et al (2010). Average adenovirus DNA concentrations in sewage and CSOs were 1.15×10(6) viruses/liter and 5.35×10(5) viruses/liter, respectively, while the adenovirus removal was calculated at <2 log(10) (99 %) for this WWTP (Fong et al 2010).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…One of the sources of these parasites can be treated wastewater from wastewater treatment plants (Hachich et al 2013;Sroka et al 2013). In an attempt to enrich poor existing data on the prevalence of these parasites in wastewater effluents in Greece, the study produced very interesting data from the parasitological analysis of the sewage samples of the study (Spanakos et al 2015).…”
Section: Microbiological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the JRC draft report it is indicated that information is often not available on concentrations, dose-response relationships and disease burden for various waterborne pathogens in treated wastewater in Europe. However, the EFSA experts have identified various scientific papers addressing some of the most relevant pathogens (Montemayor et al, 2005;Levantesi et al, 2010;Rodríguez-Manzano et al, 2012;Rusiñol et al, 2015;Spanakos et al, 2015;Eftim et al, 2017). This should by no means be considered as an extensive literature search on the topic, but is given as an illustration that relevant data are available that address the previous point.…”
Section: Answer To Tor3mentioning
confidence: 99%
“…Robertson et al (2006). Furthermore, studies from Europe (Greece and Spain) also describe the common occurrence of Cryptosporidium in tertiary-treated wastewater (Montemayor et al, 2005;Spanakos et al, 2015).…”
Section: Answer To Tor3mentioning
confidence: 99%